Knowledge, attitude, and self-efficacy of pre-service teachers in response to sexuality education to children - Ding, Yumo; Bakar, Kamariah Abu; Ismail, Nurul Khairani (International Journal of Innovative Research and Scientific Studies, 2025)
Sexuality education plays a crucial role in promoting individual sexual well-being and social welfare. However, teachers' understanding of and engagement in sexuality education are still insufficiently studied, especially in the Chinese cultural context. The present study aimed to explore pre-service teachers' knowledge, attitudes, and self-efficacy regarding children's sexuality education and bridge the existing research gap with empirical data. A quantitative research method was employed to gather data from 458 pre-service teachers in China through an online questionnaire, and the data were analyzed through descriptive statistical analysis and PLS-SEM. The findings indicated that while many pre-service teachers had relatively positive attitudes towards children's sexuality education and expressed moderate to high levels of self-efficacy in teaching school-based sexuality education, they showed significant weaknesses in their knowledge of sexuality education with overall poor knowledge levels. Furthermore, the study found that there were significant positive effects of participants' knowledge on attitudes, attitudes on self-efficacy, and knowledge on self-efficacy. The study emphasizes the necessity of systematic training for pre-service teachers at the higher educational level to facilitate the effective implementation of school-based sexuality education by raising teachers' understanding of sexuality-related topics and improving their attitudes toward sexuality education. Future studies are proposed to further address the interaction of multiple influencing factors, adopt a mixed research approach, investigate longitudinal influences, and make cross-cultural comparisons to construct a more comprehensive framework. Such findings have yielded valuable insights for policymakers and educators to formulate and develop a more effective framework for sexuality education.